The Uncertainty of Noise Composed of Separate Sound Events - Rufin MAKAREWICZ; Roman GOŁĘBIEWSKI (Archives of Acoustics)
Transportation noise is a main source of noise pollution. It is assumed that it consists of recognizable noise events which come from moving aircrafts, trains and boats. The noise of an isolated sound event is assessed by the sound exposure level, $L_{AE}$. Much legislation and many regulations and guidelines employ the A-weighted time-average sound level, $L_{Aeq,T}$, with the time interval $T$ of one hour or longer. $L_{AE}$ measurements enable an approximation of $L_{Aeq,T}$. The key point is the uncertainty of this approximation. It has been shown that an increase in the number of $L_{AE}$ categories brings about a decrease in uncertainty. For illustrative purposes, $L_{AE}$ measurements of aircrafts taking off and landing were carried out.